Photographic treatment in newspaper sites from Porto University. Descriptive analysis based on quality indicators - López del Ramo, Joaquín (Revista General de Información y Documentación, 2015)
This work gives an account of his investigation in 2014 that deals with the description and characterization of the general treatment of the photograph in three newspaper portals sponsored by the Universidade do Porto with high standards of quality (P3, JPN and Ciência 2.0). On the methodological choice of content analysis, using as a tool for data collection a book of multidimensional codes own comes to the conclusion that there are strengths and gaps between the three common means object of study, which do not differ in excess of those detected by other studies to professional media digital press.The main strengths with a high degree of use of photographic content, layout and correct consistency interactivity. Next to the abuse of very small photographs, the main problem identified is that the pictures have very little information value, limited in most cases to a decorative function.